Cubo: Communication System for Children with Autism Spectrum Disorders - Martins, Sofia (2020)
The current research, focusing on Social Innovation and Inclusive Design, seeks to understand and explore the interpersonal communication of children with autism spectrum disorders. The main objective is to contribute to the development of the cognitive and social skills of these children, improving and facilitating their difficulties in three domains: verbal language and communication; interpersonal relationships and in the field of thought and behavior. In order to help solving these problems, Cubo has been developing, an innovative system of universal and inclusive communication, composed of a new universal and alternative/augmentative alphabet and digital object that promotes autonomy, social integration, personal development and interpersonal relationships. This first paper aims to inform and promote the discussion of the process and results of the ongoing research, describing the first phases of the design process itinerary and methods applied, as well as the description of the following phases that cause multidisciplinarity and co-creation.